THE HISTORY OF THE CREATION OF THE LEZGIN (KAKHETI) CORDON LINE: GOALS AND TASKS OF FORTIFICATIONS IN THE DEVELOPMENT OF THE REGION - Газиева, Абидат Абдулаевна; Озтурк, Мустафа (History, Archeology and Ethnography of the Caucasus, 2022)
The beginning of the 19th century marks a new stage in the military-political development of the Eastern Caucasus and Transcaucasia. Since Georgia was annexed to the empire at that time, the state faced the issue of protecting new territories. A. Ermolov initiated a period of vigorous activity of topographers of the region associated with the construction of a number of fortresses and transfer from the policy of punitive operations to the systematic development of the region using civil colonization. For this purpose, the construction of a system of fortresses along the Iori and Alazani rivers began in the 30s of the 19th century. This system of fortresses entered historiography as the Lezgi (Kakheti) cordon line which was a component of the Left flank of the Caucasian cordon line (after the division of the Caucasian cordon line into flanks in 1834). The Russian government entrusted a number of military-political and economic tasks to the new cordon. In addition, the article examines the place and role of the command staff of the cordon line in the construction, re-deployment of the forces on the line, and the putting into practice provisions of the Caucasian policy in the region. The work reveals the military-political, social-economic importance of the line and the history of the creation of a cordon on the border with Georgia based on the available sources. Overall, the transformation of the Caucasian policy in the region can be seen on the example of the Lezgi (Kakheti) cordon line (the change of policy’s vector from defensive (tactics of punitive operations) to the civil colonization of the region that subsequently contributed to the approach with highlanders through economic, cultural and household relations. The number of constructions on the line and the number of forces deployed in fortresses and fortifications were changing depending on the success of the Tsarist Army in the mountains. The line from the moment of its creation and in the subsequent period performed defensive functions not only for the internal borders but also served as a support of the southern borders of Russia from Turkey and Iran. It was the primary task of preserving the region in geopolitical terms.
Keywords: Left flank of the Caucasian cordon line; fortification; post; Djar; Zakatala; Georgia; Georgian Military Highway; cordon line; geopolitics; Caucasian polic